Income Distribution, Factor Endowments, and Trade Openness - Antonio Spilimbergo; Juan Luis Londo\~no; Miguel Székely (Inter-American Development Bank, Office of the Chief Economist, 1997)
This paper studies the empirical links among factor endowments, trade, and personal income distribution. The motivation is that many developing countries have implemented radical trade reforms in recent years. These reforms have changed relative prices, induced a reallocation of resources, and may have led to the introduction of new production techniques. These changes are quite complex and their final effect on income distribution is theoretically unclear. The author`s aim is to present the stylized empirical facts on the relations between income distribution, factor endowments, and trade.
Keywords: 330